2015
DOI: 10.1111/jnc.13128
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of p53 up‐regulated modulator of apoptosis by JNK/c‐Jun pathway in β‐amyloid‐induced neuron death

Abstract: Neuronal loss in selective areas of brain underlies the pathology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 63 publications
(92 reference statements)
2
47
0
Order By: Relevance
“…The increase in Puma expression and appearance of the second band occurred to a similar extent in Caspase-9 knockout cultures (Figure S3C), which are protected from degeneration (Simon et al, 2012), indicating that both the rise of overall Puma levels and the appearance of the second band are not simply a secondary consequence of the degenerative process. Pharmacological inhibition of JNK prevented this TD-induced rise in Puma (Figure 4E), consistent with a known role of c-Jun in promoting Puma expression (Akhter et al, 2015) and providing a mechanism for the somatic requirement for JNK signaling that we observed (Figure 2G,H). Puma has also been identified as a transcriptional target of Foxo3a (You et al, 2006), and accordingly we found that shRNA-mediated knockdown of Foxo3a in sensory neurons largely blocked the rise in Puma levels that accompanies TD (Figure 4F).…”
Section: Resultssupporting
confidence: 87%
“…The increase in Puma expression and appearance of the second band occurred to a similar extent in Caspase-9 knockout cultures (Figure S3C), which are protected from degeneration (Simon et al, 2012), indicating that both the rise of overall Puma levels and the appearance of the second band are not simply a secondary consequence of the degenerative process. Pharmacological inhibition of JNK prevented this TD-induced rise in Puma (Figure 4E), consistent with a known role of c-Jun in promoting Puma expression (Akhter et al, 2015) and providing a mechanism for the somatic requirement for JNK signaling that we observed (Figure 2G,H). Puma has also been identified as a transcriptional target of Foxo3a (You et al, 2006), and accordingly we found that shRNA-mediated knockdown of Foxo3a in sensory neurons largely blocked the rise in Puma levels that accompanies TD (Figure 4F).…”
Section: Resultssupporting
confidence: 87%
“…The formation of amyloid plaques is a major factor in AD, thus, determining the underlying mechanism by which Aβ induces neuronal cell death is crucial. A recent study demonstrated that dying cells in AD brains and cultures of neurons exposed to Aβ exhibit the characteristics of apoptosis (2). However, the specific signaling pathways by which Aβ triggers cell apoptosis have not been well defined.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that Aβ is toxic to neurons [2224]. Our previous study has shown that the hASC extract promotes cell survival in a model of mutant Huntingtin-induced cell death [25].…”
Section: Resultsmentioning
confidence: 99%